2008
DOI: 10.1002/pmic.200700574
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteomic identification of the hypothetical protein NMB1468 as a novel lipoprotein ubiquitous in Neisseria meningitidis with vaccine potential

Abstract: Many potential vaccine candidates for serogroup B Neisseria meningitidis (NMB) have been identified by reverse vaccinology, a genome-based approach. However, some candidates may be unseen owing to uncertain annotation or their peculiar properties. In this study, we describe the preparation and identification of a novel lipoprotein expressed in all meningococcal strains tested. mAb were first prepared from mice immunized with a meningococcal B strain isolated in Taiwan. Total proteins from the immunizing strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 45 publications
0
46
0
Order By: Relevance
“…In this context, it is interesting that other studies have reported evidence indicating that some of the glycoproteins identified in N. gonorrhoeae and now in N. meningitidis are exposed at the bacterial surface. These glycoproteins include a putative peptidyl-prolylisomerase (NGO1225) (38), GNA1946 (45), Ag473 (NGO1043) (28), and the nitrite reductase AniA (NGO1276) (37). It is also worth mentioning that the original evidence that AniA is expressed in vivo was derived from detection of AniA-reactive antibodies in diseased patients but not in normal human sera (12).…”
Section: Figmentioning
confidence: 99%
“…In this context, it is interesting that other studies have reported evidence indicating that some of the glycoproteins identified in N. gonorrhoeae and now in N. meningitidis are exposed at the bacterial surface. These glycoproteins include a putative peptidyl-prolylisomerase (NGO1225) (38), GNA1946 (45), Ag473 (NGO1043) (28), and the nitrite reductase AniA (NGO1276) (37). It is also worth mentioning that the original evidence that AniA is expressed in vivo was derived from detection of AniA-reactive antibodies in diseased patients but not in normal human sera (12).…”
Section: Figmentioning
confidence: 99%
“…The development of protein microarrays and immunoproteomics let us identify novel immunogens that induce humoral immune responses in a high-throughput manner (1,12,19,21,27,28). The approach to identify T-cell antigens on a large scale is under way (10,14).…”
mentioning
confidence: 99%
“…A number of methods have been developed to enable high-throughput display of the proteome of a pathogen to the host immune system. Immunomics (also known as serological proteome analysis [SERPA]) combines proteomic-based approaches with serological analysis and has been widely applied for antigen discovery and vaccine development (72)(73)(74). Applied to S. aureus, this approach led to the identification of 15 highly immunogenic proteins, including known and novel vaccine candidates (75).…”
Section: Immunomics: Identification Of Immunogenic Proteinsmentioning
confidence: 99%